Bringing Good Governance Home in Indonesia - Jabali, Fuad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
The centre for the Study of Islam and Society (PPIM-CENSIS), based as The State Institute for Islamic Studies (IAIN) Syarif Hidayatullah Jakarta, continues to develop research programs that contribute to strengthening both the scientific tradition as well as community development in Indonesia. One of our current research programs, undertaken in collaboration with the Ford Foundation, focuses on the issue of good governance in Indonesia. Targeting the Muslim community, this project entails a combination of research, education and publications. The crux of the project ascertaining is to what extent Islam and the Muslim community in general support or reject the relative values of good governance such as democracy, tranparency, participation and accountability.DOI: 10.15408/sdi.v8i3.686